DAMPAK KETERBUKAAN EKONOMI TERHADAP PENYERAPAN TENAGA KERJA INDUSTRI KONVEKSI DI PROVINSI JAWA BARAT PERIODE 2010-2013 - Heidinar Megajulian Kusdianto; Firman Rosjadi Djoemadi; Idfi Setyaningrum (Perpustakaan Universitas Surabaya, 2018)
This study was conducted with the aim of identifying the effects of the Impact of Economic Openness (including Export Intensity, Import Raw Material, Foreign Investment), Wages and Outputs on Employment Absorption. The object used in this research is the Convection Industry in West Java Province with a period of 4 years (2010-2013). This study uses a quantitative approach. By applying panel data regression method with Fixed Effect Model with Period Weights, the result of the research shows that variables of economic openness such as import of raw materials and FDI have a positive and significant effect on labor absorption. While the export variable showed insignificant results. In addition, factors such as wages and outputs also have a significant effect on labor absorption.